2011
DOI: 10.1016/j.jhep.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 enhances apoptosis and insulin resistance in a rat model of alcoholic liver disease

Abstract: Chronic ethanol consumption in the Long-Evans (LE) rat has been associated with hepatic p53 activation, and inhibition of the insulin/PI3K/AKT signal transduction cascade due to increased expression of phosphatase and tensin homologue deleted on chromosome 10 (PTEN). We hypothesize that p53 activation and altered insulin signaling may influence the susceptibility of rats to ethanol-induced liver damage. Furthermore, p53 not only activates programmed cell death pathways and suppresses hepatocellular survival si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 35 publications
3
117
0
Order By: Relevance
“…Moreover, the RNA-binding protein HuR stabilizes SIRT1 mRNA through 3Ј-UTR interactions, leading to increased SIRT1 levels (34). Given that both p53 and HuR have been implicated in alcoholic liver disease, it is logical to speculate that ethanol-mediated up-regulation of miR-217 may affect p53 or HuR that bind to the 3Ј-UTR of SIRT1 and hence may lead to suppression of SIRT1 expression (35,36). On the other hand, our data cannot rule out the possibility that other miRNAs may also play roles in governing SIRT1 expression in response to ethanol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the RNA-binding protein HuR stabilizes SIRT1 mRNA through 3Ј-UTR interactions, leading to increased SIRT1 levels (34). Given that both p53 and HuR have been implicated in alcoholic liver disease, it is logical to speculate that ethanol-mediated up-regulation of miR-217 may affect p53 or HuR that bind to the 3Ј-UTR of SIRT1 and hence may lead to suppression of SIRT1 expression (35,36). On the other hand, our data cannot rule out the possibility that other miRNAs may also play roles in governing SIRT1 expression in response to ethanol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inhibition of p53-dependent apoptosis reduced LPSinduced liver injury [19]. A recent report showed that p53 activation correlated with susceptibility to ethanol-induced liver damage, a pathologic condition that is thought to mechanistically resemble NASH [20]. In addition, hepatic p53 expression and hepatocyte apoptosis increase in patients with NASH and a mouse model of NASH [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In a NASH mice model, based on methionine and choline deficient diet, the level of apoptosis was decreased in the livers of p53-deficient mice compared to WTp53 mice [26]. Similarly, ethanol-induced hepatocyte apoptosis was abrogated in p53 null mice [27] while activation of p53 enhanced apoptosis in a rat model of alcoholic liver disease [28]. These observations suggest that p53 is necessary for the apoptotic response following ROS formation in both ethanolexposed and diet-deficient mice models.…”
Section: Activation Of Wtp53 Promotes Fatty Liver Pathologiesmentioning
confidence: 87%
“…Interestingly, a recent study has suggested another mechanism by which p53 affects insulin resistance. This study suggested that activation of TIGAR, a metabolic target of p53, may decrease glycolysis and favor gluconeogenesis, resulting in elevated levels of glucose [28]. High glucose levels activate sterol regulatory element-binding protein 1c (SREBP1c) which in turn promotes steatosis and affects insulin receptor substrate 2 (IRS-2) inhibitions [32].…”
Section: Activation Of Wtp53 Promotes Fatty Liver Pathologiesmentioning
confidence: 99%